The Relationship Between Coping Mechanisms and Anxiety Levels in Hemodialysis Patients at Dr. M.M. Dunda Limboto Regional General Hospital - Firmawati; Nur Uyuun I. Biahimo; Nurfadilah Tantu (Universitas Muhammadiyah Palu, 2026)
Hemodialysis is a crucial procedure for patients with chronic kidney failure, but it can cause anxiety due to uncertainties related to the therapy, duration, and costs. Coping mechanisms play a role in managing this anxiety. This study aims to analyze the relationship between coping mechanisms and anxiety levels in hemodialysis patients at RSUD Dr. M.M. Dunda Limboto. Using a quantitative design with a cross-sectional approach, a sample of 30 respondents was selected through purposive sampling. Data were collected through questionnaires and analyzed using Chi-square tests. The results show that 50% of patients use adaptive coping mechanisms, while 50% use maladaptive ones. A total of 55.26% of respondents experienced moderate anxiety, while 44.74% experienced severe anxiety. The Chi-square test indicates a significant relationship between coping mechanisms and anxiety levels (p-value = 0.003, p < 0.05). This study suggests the need for psychological interventions to help patients develop adaptive coping mechanisms to reduce anxiety and improve their quality of life